APOE and MAPT Are Associated With Dementia in Neuropathologically Confirmed Parkinson's Disease - Tunold, Jon-Anders; Geut, Hanneke; Rozemuller, J. M. Annemieke; Henriksen, Sandra Pilar; Toft, Mathias; van de Berg, Wilma D. J.; Pihlstrøm, Lasse (Frontiers in Neurology, 2021)
Introduction: Cognitive decline and dementia are common and debilitating non-motor phenotypic features of Parkinson’s disease with a variable severity and time of onset. Common genetic variation of the Apolipoprotein E (APOE) and micro-tubule associated protein tau (MAPT) loci have been linked to cognitive decline and dementia in Parkinson's disease, although studies have yielded mixed results. To further elucidate the influence of APOE and MAPT variability on dementia in Parkinson's disease, we genotyped postmortem brain tissue samples of clinically and pathologically well-characterized Parkinson’s donors and performed a survival analysis of time to dementia. Methods: We included a total of 152 neuropathologically confirmed Parkinson's disease donors with or without clinical dementia during life. We genotyped known risk variants tagging the APOE ε4 allele and MAPT H1/H2 inversion haplotype. Cox proportional hazards regression analyses adjusted for age at onset, sex and genetic principal components were performed to assess the association between the genetic variants and time from motor onset to onset of dementia. Results: We found that both the APOE ε4 allele (HR 1.82, 95 % CI 1.16-2.83, p=0.009) and MAPT H1-haplotype (HR 1.71, 95 % CI 1.06-2.78, p=0.03) were associated with earlier development of dementia in patients with Parkinson’s disease. Conclusion: Our results provide further support for the importance of APOE ε4 and MAPT H1-haplotype in the aetiology of Parkinson's disease dementia, with potential future relevance for risk stratification and patient selection for clinical trials of therapies targeting cognitive decline in Parkinson's disease.